Multiple physical urticarias. Issue 987 (29th January 2008) - Torchia, D; Francalanci, S; Bellandi, S; Fabbri, P
Abstract : Physical urticarias are a group of mucocutaneous disorders characterised by the appearance of whealing and/or angioedema and induced by physical stimuli. A 24-year-old Caucasian male affected by ultraviolet A-induced solar urticaria, specific food-dependent exercise-induced anaphylaxis, symptomatic dermographism and allergic rhinoconjunctivitis is described.